Ethnicity and the political reconstruction of Afghanistan - Conrad Schetter (University of Bonn, Center for Development Research (ZEF), 2005)
Almost all policymakers, journalists and researchers recognize the ethnic fissions and fractions as the predominant lines of conflict in Afghanistan. What this approach ignores is the fact that, despite the ethnicization of the conflict, the ethnicization of the Afghan people themselves failed. Although ethnicity became a political-military force to reckon with during the 23 years of ongoing war in Afghanistan, the significance of ethnicity as basis of political articulation and social organisation remained very limited. Hence ethnicity has been opposed by competing identities as well as by strategic considerations of the war factions. This article will, firstly, discuss the particular meaning of ethnicity in Afghanistan in past and present, and, secondly, how the international community has dealt with ethnicity in its endeavour to bring peace to Afghanistan and to rebuild a political system. Ethnicity has emerged as one of the most problematic and precarious obstacles for the political reconstruction and state building process in Afghanistan. As in many other violent conflicts tinged by ethnicity the general question is to what extent the consideration of ethnicity - mostly in the form of proportional representation - is a political tool that will supersede or aggravate ethnic tensions. The dilemma of how to cope with ethnicity in process of peace building, state reconstruction and national formation always arises in accordance with the question of what constitutes ethnicity in the particular country and what the boundaries and relationships between ethnic groups are. This question of how to define 'ethnicity' and 'ethnic groups' is discussed extremely controversially in the academic world as well as in the arena of policy-making. Regarding Afghanistan, most researchers and policy-makers either explicitly or implicitly share the view that ethnic groups have existed since time immemorial. They assume that ethnic groups are solid cultural units which are divided by obvious boundaries and have engaged in conflicts for hundreds of years. Set against that opinion, this article argues that the meaning of ethnicity has always been very blurred in Afghanistan, and usually the so-called ethnic groups enclose a socially and culturally amorphous set of people and still do not constitute the main reference of identity and solidarity for the population, even if the war is tinged by ethnicity.
urn:nbn:de:0202-2008091124
Keywords: 300